Conceptual Model for e-Learning of Kolej Poly-Tech MARA - Fatimah, Saleh (2011)
E-learning, one of the tools emerged from information technology, has been integrated in many university programs. There are several factors that need to be considered while developing or implementing university curriculums that offer e-learning based courses. Nowadays, e-Learning is the most popular tools in the education especially for higher education. E-Learning is an online education tools for higher education and people in corporations. However, certain of the higher institutions did not use an e-Learning in the education. This project will focus on developing a prototype of e-Learning for staff in Kolej Poly Tech MARA (KPTM). This project will use two methodologies to implement this project. The first methodology is the research methodology using The Workflow of the System Development Process. While the second methodology for the methodology system using The Prototype Methodology. The aim of this project is proposes to address a conceptual model for designing and developing an adaptive e-Learning system that main application is the identification of educational needs of employees. At the end of this project, a prototype will be developed based on requirements and user acceptance using an existing e-Learning system.